Biogenesis of ZnO nanoparticles using Pandanus odorifer leaf extract: anticancer and antimicrobial activities. Issue 27 (16th May 2019) - Hussain, Afzal; Oves, Mohammad; Alajmi, Mohamed F.; Hussain, Iqbal; Amir, Samira; Ahmed, Jahangeer; Rehman, Md Tabish; El-Seedi, Hesham R.; Ali, Imran
Abstract : The continuously increasing incidence rates of cancer and infectious diseases are open threats to the sustainable survival of animals and humans. Abstract : The continuously increasing incidence rates of cancer and infectious diseases are open threats to the sustainable survival of animals and humans. In the last two decades, the demands of nanomaterials as modern therapeutic agents have increased. In this study, biogenic zinc oxide nanoparticles (ZnO NPs) were developed from aqueous Pandanus odorifer leaf extract (POLE) and characterized using modern methods and tools, such as electron microscopy, X-ray diffraction, energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy and UV-vis spectroscopy, which indicated the formation of very pure, spherical NPs approximately 90 nm in size. The anticancer activity of the ZnO NPs was evaluated by MTT and neutral red uptake (NRU) assays in MCF-7, HepG2 and A-549 cells at different doses (1, 2, 5, 10, 25, 50, 100 μg ml −1 ). Moreover, the morphology of the treated cancer cells was examined by phase contrast microscopy. The results suggest that the synthesized ZnO NPs inhibited the growth of the cells when applied a concentration from 50–100 μg ml −1 . Moreover, the biogenic ZnO NPs were analysed as an antimicrobial agent against pathogenic bacteria. The highest antibacterial activity was observed against Gram-positive Bacillus subtilis (26 nm) and Gram-negative Escherichia coli (24 mm) at 50 μg per well. Complete bacterial growth (100%) vanished 100% upon treatment with ZnO NPs at 85 μg ml −1 . Overall, POLE mediated derived biogenic ZnO NPs could serve as a significant anticancer and antimicrobial agent and be used in the development of novel drugs and skin care products.